CORPORATE GOVERNANCE, UKURAN PERUSAHAAN, DAN LEVERAGE TERHADAP MANAJEMEN LABA PERUSAHAAN MANUFAKTUR INDONESIA - Jao, Robert; Pagalung, Gagaring (Department of Accounting, Faculty of Economics & Business,Diponegoro University, Indonesia, 2011)
The aims of the research are to find out (1) influence of corporate governance which is arecategorized into managerial ownership, institutional ownership, board size, boardcomposition of independent commissioners, and audit committees on earnings management,(2) influence of firm size on earnings management, (3) influence of leverage on earningsmanagement. This study drew 28 samples from manufacturing companies listed in IndonesiaStock Exchange with a purposive sampling technique. The research data was collected fromannual reports within a period 2006 to 2009 of the Capital Market Reference Centre ofIndonesian Stock Exchange. The method of analysis was multiple linear regressions. Theresults of the study indicated that (1) corporate governance with managerial ownership,board composition of independent commissioners, and audit committee had significantnegative influence on earnings management, while institutional ownership and board size hadsignificant positive influence on earnings management, (2) firm size had significant negativeinfluence on earnings management, (3) leverage had not significant influence on earningsmanagement.Keywords:corporate governance, firm size, leverage, earnings management, annual report